Forms of work on the development of methodological competence of technology teachers in the postgraduate education system - Pokroeva, L.; Ostapenko, A. (Problems of Engineer-Pedagogical Education, 2021)
The public policy on education in Ukraine is aimed to reform the system of education by the principles of humanism, humancentrism, person oriented and competence approach; to imply the best world experience, to democratize the system of education, the academic freedom of a teacher. This article describes what forms of work for developing the methodological competence of a technology teacher are used in the postgraduate education system. It is described the objectives of teachers training at different stages of methodological competency development during their attendance of the skills development courses, such as: diagnostic, motivational, activity-technological, reflexive, taking into account the peculiarities of every component of teacher’s methodological competency and modern principles of educational process construction in the institution of postgraduate pedagogical education. The article contains the analysis of the scientific sources that shows the existence of the significant number of works dedicated to the implementation of the competency approach in the professional teacher training. At the same time, the issue of teachers’ technologies methodological competency development at different stages of their professional activity and during their attendance of the skills development courses is researched insufficiently. The peculiarities of teacher training at every stage of development of methodological competency are outlined in accordance with the Law of Ukraine “On Education” (2017), considering the principles of Conception of the New Ukrainian School, objectives of the State Standard of General Secondary Education as basis of substantive content of educational process and current curriculum on manual skills and technologies. The article defines the purpose of technology teachers advanced training; describes the structural components of the methodological competence of a technology teacher; the stages of development of methodological competence. The forms of work, respectively, at each stage are characterized. The structural components of the methodological competence determine the content and forms of work with teachers during training in continuing education courses. The article also lists the criteria for innovative forms of work with technology teachers in continuing education courses and methodological activities. The conditions for the design of organization innovative forms of the educational process in the advanced training system for teacher-technologists are determined.